The Homosexual Role - McIntosh, Mary (Social Problems, 1968)
The current conceptualization of homosexuality as a condition is a false one, resulting from ethnocentric bias. Homosexuality should be seen rather as a social role. Anthropological evidence shows that the role does not exist in all societies, and where it does it is not always the same as in modern western societies. Historical evidence shows that the role did not emerge in England until towards the end of the seventeenth century. Evidence from the "Kinsey Reports" shows that, in spite of the existence of the role in our society, much homosexual behavior occurs outside the recognized role and the polarization between the heterosexual man and the homosexual man is far from complete.
Keywords: 1900-1999; 1960-1969; LGBTQIA2+; cours; discipline; homosexualité; premier cycle; périodes historiques; santé; sciences humaines; sexualité; soc2014; sociologie; thématiques

l'indéfinissable malaise - Friedan, Betty (La femme mystifiée, 1964)
Première publication:1963
Keywords: 1900-1999; amériques; cours; discipline; fem1000; féminisme libéral; premier cycle; périodes historiques; régions géographiques; sciences humaines; sociologie; états-unis

Le travail ménager s'accroît en fonction du temps dont dispose la ménagère - Friedan, Betty (La femme mystifiée, 1964)
Première publication:1963
Keywords: 1900-1999; amériques; cours; discipline; division sexuelle du travail; fem1000; premier cycle; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques; travail; états-unis

Chapitre XVII Sexe Et Tempérament et Conclusion dans Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée - Mead, Margaret; Chevassus, Georges (Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée, 1963)
Dans le texte Adolescence à Samoa (1928), l'auteure soutient que l'adolescence n'est pas une étape nécessaire entre l'enfance et l'âge adulte. Dans le texte Trois sociétés primitives de Nouvelle-Guinée (1935), elle analyse, à partir de ses observations de terrain, les différences de caractère entre hommes et femmes.
Section: 606 pages : illustrations ; 18 cm
Keywords: anthropologie; approches et analyses; corps; cours; discipline; océanie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques